Tożsamość deliberatywna = Deliberative identity - Zgiep, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The goal of the article is to introduce into the humanities and social sciences the notion of "deliberative identity" which accounts for a truly (post)modern phenomenon encompassing individualistic and collectivistic anthropology. The concept is derived from contemporary democratic discourse influenced greatly by the theory of deliberative democracy.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie